Jezebel or Jerusalem: Revelation, Ecclesiastical Purity, and the Christian Response(s) - Putt, Sharon L. (Interpretation, 2026)
This essay delves into the identity, symbolism, and ethical implications of the four women in John’s apocalypse, the book of Revelation. The juxtaposition of “evil” and good with the characters “Jezebel” in the letter to Thyatira, the harlot of Babylon, the Woman Clothed with the Sun, and the Bride of Christ/New Jerusalem communicate essential messages to contemporary readers. By studying the ancient biblical world, its texts, and its symbols, these women move from mere characters in a confusing story to teachers—through both good and bad examples—who speak truth to power in current affairs such as politics, economics, and religion.